A clinical audit into the adherence of foot health management standards of rheumatoid arthritis compared with the foot health management standards of diabetes mellitus in North-East London. Issue 1 (28th January 2021) - Joyce, Christopher; Rajak, Rizwan
Abstract: Objectives: RA has an affinity for smaller joints, thus its effect on the foot/ankle is widely known. Despite this, there is lack of adherence to foot management standards by podiatrists. This research aimed to audit the adherence to these standards and compare them with well-established adherence to management standards in the diabetic foot. Methods: In this clinical audit, data were obtained via six National Health Service (NHS) podiatry departments in North-East London on service provision, management, treatment and professional development on both RA and diabetic foot health via foot management clinical audit tools. Descriptive analyses were conducted and analysed to identify patterns and trends, with set standard compliance conditions calculated on the Net Promotor Score (NPS) metric to allow for multi-comparison. Results: All areas of RA foot health management were found to have poor compliance when compared with diabetes foot health management. When using NPS, no trust audited met the majority of foot health standards in RA, with only two having a positive score (meeting the minimum standards), compared with all trusts posting a positive NPS on diabetes foot health standards. Conclusion: Our results indicate that poor compliance to RA foot health standards is prevalent across the audited region and might be resulting in worsening foot outcomes despite a paradigm shift in other areas of RA management. Enhanced training and knowledge are required for better adherence to the standards set out and to improve foot health management in RA.